2021
DOI: 10.1212/nxi.0000000000001012
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD20 Depletes Meningeal B Cells but Does Not Halt the Formation of Meningeal Ectopic Lymphoid Tissue

Abstract: ObjectiveTo investigate whether anti-CD20 B-cell-depleting monoclonal antibodies (ɑCD20 mAbs) inhibit the formation or retention of meningeal ectopic lymphoid tissue (mELT) in a murine model of multiple sclerosis (MS).MethodsWe used a spontaneous chronic experimental autoimmune encephalomyelitis (EAE) model of mice with mutant T-cell and B-cell receptors specific for myelin oligodendrocyte glycoprotein (MOG), which develop meningeal inflammatory infiltrates resembling those described in MS. ɑCD20 mAbs were adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 36 publications
5
21
0
Order By: Relevance
“…Unless a treatment is administered that is neuroregenerative, no improvement in clinical score can be expected. In further support of our study, Brand et al, 2021 [ 61 ] also did not observe any changes in the clinical course of spontaneous chronic EAE after anti-CD20 treatment despite efficient depletion of B cells in the periphery.…”
Section: Discussionsupporting
confidence: 92%
“…Unless a treatment is administered that is neuroregenerative, no improvement in clinical score can be expected. In further support of our study, Brand et al, 2021 [ 61 ] also did not observe any changes in the clinical course of spontaneous chronic EAE after anti-CD20 treatment despite efficient depletion of B cells in the periphery.…”
Section: Discussionsupporting
confidence: 92%
“… 22 Recently, we demonstrated that anti-CD20 monoclonal antibodies, despite its superior efficacy in treating RMS and moderate efficacy in treating primary progressive MS, neither ameliorated EAE nor reduced the extent of mELT formation in the 2D2xTh mouse model. 20 Apparently, anti-CD20 monoclonal antibodies only depleted B cells from mELT without changing any other obvious features. Of interest, a very recent study demonstrated that evobrutinib, a Bruton tyrosine kinase inhibitor, reduced the areas of meningeal contrast enhancement in an EAE model in Swiss Jim Lambert J mice immunized with proteolipid protein peptide (PLP139-151) using serial ultra-high-field MRI.…”
Section: Discussionmentioning
confidence: 96%
“…Spleen cells were processed and analyzed as previously published. 20 The following anti-mouse antibodies were used: CD16/CD32 (BD, 2.4G2), CD45.2 (BioLegend, 104, FITC), CD19 (BioLegend, 6D5, PerCP), CD45R/B220 (BioLegend, RA3-6B2, AF647), CD3e (BD, 145-2C11, PE), and CD4 (BD, RM4-5, PB).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The animal model 2D2xTh leads to spontaneous development of EAE with meningeal lymphoid follicles but does not require B cells for pathology. Depleting peripheral B cells before the EAE onset did not halt the production of these follicles nor reduce clinical severity [ 169 ]. Depleting peripheral B cells after the onset of EAE also did not affect the number or size of the meningeal follicles.…”
Section: Effects Of Ms Therapies On B Cell Migrationmentioning
confidence: 99%